Multicomponent synthesis of spiropyrrolidine analogues derived from vinylindole/indazole by a 1,3-dipolar cycloaddition reaction - Narayanarao, Manjunatha; Koodlur, Lokesh; Revanasiddappa, Vijayakumar G.; Gopal, Subramanya; Kamila, Susmita (Beilstein Journal of Organic Chemistry, 2016)
A new series of spiropyrrolidine compounds containing indole/indazole moieties as side chains have been accomplished via a one-pot multicomponent synthesis. The method uses the 1,3-dipolar cycloaddition reaction between N-alkylvinylindole/indazole and azomethine ylides, prepared in situ from cyclic/acyclic amino acids. The 1,3-dipolar cycloaddition proceeds efficiently under thermal conditions to afford the regio- and stereospecific cyclic adducts.
Keywords: L-proline; ninhydrin; sarcosine; spiropyrrolidine; 5-vinylindazole; 5-vinylindole

(untitled) - Almansour, A. I.; Ali, S.; Ali, M. A.; Ismail, R.; Choon, T. S.; Sellappan, V.; Elumalai, K.; Pandian, S. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Wei, A. C.; Ali, M. A.; Yoon, Y. K.; Ismail, R.; Choon, T. S.; Kumar, R. S.; Arumugam, N.; Almansour, A. I.; Osman, H. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Ali, M. A.; Ismail, R.; Choon, T. S.; Yoon, Y. K.; Wei, A. C.; Pandian, S.; Kumar, R. S.; Osman, H.; Manogaran, E. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Rao, J. N. S.; Raghunathan, R. (Tetrahedron Lett., 2012)

(untitled) - Ardill, H.; Grigg, R.; Sridharan, V.; Surendrakumar, S. (Tetrahedron, 1988)

(untitled) - Maheswari, S. U.; Balamurugan, K.; Perumal, S.; Yogeeswari, P.; Sriram, D. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Rehn, S.; Bergman, J.; Stensland, B. (Eur. J. Org. Chem., 2004)

(untitled) - Manian, R. D. R. S.; Jayashankaran, J.; Raghunathan, R. (Tetrahedron, 2006)

(untitled) - Alizadeh, A.; Moafi, L. (Synlett, 2016)

(untitled) - Li, G.; Wu, M.; Li, F.; Jiang, J. (Synthesis, 2015)

(untitled) - Gaikwad, D. D.; Chapolikar, A. D.; Devkate, C. G.; Warad, K. D.; Tayade, A. P.; Pawar, R. P.; Domb, A. J. (Eur. J. Med. Chem., 2015)

(untitled) - Prasanna, P.; Balamurugan, K.; Perumal, S.; Yogeeswari, P.; Sriram, D. (Eur. J. Med. Chem., 2010)

(untitled) - Gribble, F. M.; Loussouarn, G.; Tucker, S. J.; Zhao, C.; Nichols, C. G.; Ashcroft, F. M. (J. Biol. Chem., 2000)

(untitled) - Humphrey, J. H.; Iliff, P. J.; Marinda, E. T.; Mutasa, K.; Moulton, L. H.; Chidawanyika, H.; Ward, B. J.; Nathoo, K. J.; Malaba, L. C.; Zijenah, L. S.; Zvandasara, P.; Ntozini, R.; et al. (J. Infect. Dis., 2006)

(untitled) - Sakai, W.; Swisher, E. M.; Karlan, B. Y.; Agarwal, M. K.; Higgins, J.; Friedman, C.; Villegas, E.; Jacquemont, C.; Farrugia, D. J.; Couch, F. J.; Urban, N.; Taniguchi, T. (Nature, 2008)

(untitled) - Rajeswaran, W. G.; Labroo, R. B.; Cohen, L. A. (J. Org. Chem., 1999)

(untitled) - Hegde, S.; Jayashankaran, J.; Ghosal, A.; Prasanna, T. S. R.; Shivaraj, Y.; Raju, K. M. (J. Heterocycl. Chem., 2013)

(untitled) - Greulich, T. W.; Daniliuc, C. G.; Studer, A. (Org. Lett., 2015)

(untitled) - Le Borgne, M.; Marchand, P.; Delevoye-Seiller, B.; Robert, J.-M.; Le Baut, G.; Hartmann, R. W.; Palzer, M. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Slade, D. J.; Pelz, N. F.; Bodnar, W.; Lampe, J. W.; Watson, P. S. (J. Org. Chem., 2009)

(untitled) - Molander, G. A.; Brown, A. R. (J. Org. Chem., 2006)

(untitled) - Niu, D.; Buchwald, S. L. (J. Am. Chem. Soc., 2015)

(untitled) - Lakshmi, N. V.; Thirumurugan, P.; Perumal, P. T. (Tetrahedron Lett., 2010)